POSITIVE AND NEGATIVE POLITENESS STRATEGIES REFLECTED IN "GOLDELINE" NOVEL BY JIMMY CAJOLEAS: PRAGMATIC APPROACH - Florencia Sandra Marceline; Zia Hisni Mubarak (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
Being polite should be important regardless of age. This research aimed to analyze how adults used positive and negative politeness strategies based on the politeness theory by Brown and Levinson (1987) to talk politely to a young girl and boy. The data source is a 2017 novel titled “Goldeline” which was written by Jimmy Cajoleas. The novel revolves around how Goldeline, an 11-year-old girl, ran away from the Preacher who wanted to take her life. On her journey, Goldeline met a lot of adults and as she was a young girl, the adults talked to her politely. Qualitative research method is applied to discuss the research. It is found that positive politeness was used more frequently than negative politeness. The most frequently used positive politeness strategy was the fourth strategy, which is using in-group markers; used in 23 data. As for the negative politeness, the most frequently used strategy was the seventh strategy, which is impersonalizing speaker and addressee; used in 16 data.